COMPARING THE ANTIBACTERIAL EFFICACY OF INTRACANAL MEDICAMENTS IN COMBINATION WITH CLOVE OIL AGAINST ENTEROCOCCUS FAECALIS - Madhavan, Sanjay; ., Muralidharan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To demonstrate whether clove oil enhances the antibacterial effect of intracanal medicaments. 2 Methods: Materials used include clove oil, Enterococcus faecalis microorganism, intracanal medicaments (metronidazole, ciprofloxacin, clindamycin, and calcium hydroxide), agar plates, motor, pestle, weighing machine, propylene glycol, glass slab, scale. Agar well diffusion method is employed to study the antibacterial effects of intra canal medicaments with and without clove oil against E. faecalis. Results: From the obtained results it can be concluded that intra canal medicaments combined with clove oil showed greater antibacterial effects against the microorganism, E. faecalis, than those intracanal medicaments without clove oil. Conclusion: The ultimate goals of intracanal medicaments are complete elimination of bacteria, their by-products and pulpal remnants from infected root canals and the complete seal of disinfected root canals. Clove oil can be attributed to its antimicrobial, antifungal, antiseptic, antiviral, aphrodisiac, and stimulating properties. Eugenol in clove essential oil has an inhibitory effect on various bacteria and should be used in minimum inhibitory concentration for safe and effective results. It is used to treat patients with pain from a dry socket, as well as used in a number of temporary restorative materials. Intracanal medicaments when combined with other substances may produce additive or synergistic effects. In this study, the synergistic effect of clove oil when mixed with other intracanal medicaments is tested and found to be more effective. Keywords: Intracanal medicaments, Eugenol, Clove, Intra canal infection.